PHENIX U.S.-Japan Collaboration Investigation of Thermal and Mechanical Properties of Thermal Neutron–Shielded Irradiated Tungsten. (18th August 2019) - Garrison, Lauren M.; Katoh, Yutai; Geringer, Josina W.; Akiyoshi, Masafumi; Chen, Xiang; Fukuda, Makoto; Hasegawa, Akira; Hinoki, Tatsuya; Hu, Xunxiang; Koyanagi, Takaaki; Lang, Eric; McAlister, Michael; et al.
Abstract: The United States and Japan have collaborated on fusion materials research in a series of agreements reaching back to 1981. The PHENIX collaboration is the latest U.S.-Japan project which spans 2013 to 2019 and has the goal of assessing technical feasibility of tungsten-based, helium-cooled plasma-facing component concepts for a demonstration fusion power reactor (DEMO). Task 2 within the PHENIX project is focused on evaluating the neutron irradiation effects in tungsten. For tungsten, the transmutation to Re and Os is at least as important to determining its properties after irradiation as the displacement damage, and the transmutation rate depends on the energy spectrum of the reactor. A large-scale, instrumented irradiation capsule with thermal neutron shielding to better mimic fusion conditions was irradiated in the High Flux Isotope Reactor (HFIR) at Oak Ridge National Laboratory. The tungsten specimens were irradiated in different temperature zones between 500°C and 1200°C to doses of 0.2 to 0.7 displacements per atom. More than 20 varieties of pure tungsten and tungsten alloys were included in the irradiation, and they were evaluated in the 3025E hot-cell facility and at the Low Activation Materials Development and Analysis Laboratory. The elevated temperature tensile, fracture toughness, hardness, thermal conductivity, electrical resistivity, density, elemental composition, and microstructure properties of the irradiated materials are being collected. This paper overviews the experimental design, specimen matrix, and the initial results of postirradiation examinations.